2010
DOI: 10.1111/j.1551-2916.2010.04065.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Optical Property of Glass Ceramics Containing Ruby Crystals

Abstract: We have developed the glass ceramics containing ruby crystals by heat treatment of a Cr3+‐doped SiO2–Al2O3–Y2O3 glass at 1550°C. The shape of precipitated crystals in the glass matrix was rod type whose average width and length were around 10 and 200 μm, respectively. From an X‐ray diffraction measurement and an electron probe X‐ray microanalysis, it was confirmed that the rod crystals were α‐Al2O3. Intense emission bands of Cr3+ at 694 nm, called the R‐lines, were observed in the glass ceramics heat treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“… 37 This implies that also in the present case, Cr 3+ ions enter into the strong ligand field of a crystalline precipitate. 38 , 39 Fig. 1 shows the UV-NIR absorption spectra which correspond to the above observations.…”
Section: Resultssupporting
confidence: 59%
“… 37 This implies that also in the present case, Cr 3+ ions enter into the strong ligand field of a crystalline precipitate. 38 , 39 Fig. 1 shows the UV-NIR absorption spectra which correspond to the above observations.…”
Section: Resultssupporting
confidence: 59%
“…The FAB-MS spectrum of complex 2 reveals a trinuclear structure, Eu 3 (hfa) 8 ( m -dpeb) 3 + (Figure a). The X-ray diffraction image and patterns are similar to those for glass ceramics (Figure b and c) . A circular-shaped structure shown in Figure was obtained after the structure-optimization process.…”
Section: Resultssupporting
confidence: 53%
“…We also reported that a large amount of boron in the Eu 2+ , Dy 3+ : SrAl 2 O 4 crystals promote their long‐persisting luminescence. The frozen sorbet technique is suitable for the synthesis of glass composites including desirable crystals with high‐melting temperatures such as the α‐Al 2 O 3 (ruby)‐phase (>2050°C), Y 3 Al 5 O 12 (YAG) phase (1800°C) and β‐CaSi 2 O 4 phase (2100°C) . Transparent Eu 2+ , Dy 3+ : SrAl 2 O 4 glass‐ceramics prepared using the frozen sorbet technique is novel materials that may be used for future light storage applications.…”
Section: Introductionmentioning
confidence: 99%